A ground source heat pump EICP mortar backfill material and a preparation method and application thereof
Patent Information
- Application Number
- CN202610886477.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-18
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-06-18
AI Technical Summary
[0006]为解决上述现有技术中地源热泵回填材料导热性能差、水稳定性及热稳定性不足、酶诱导碳酸盐沉淀材料碳酸钙沉积效率低、高低温循环下性能衰减明显等问题,本申请提供一种地源热泵EICP砂浆回填料,其技术方案如下:
通过采用羟丙基甲基纤维素与黄原胶作为复配增稠剂,并引入碳纤维与牡蛎壳粉作为复配导热增强材料,同时严格控制基础骨料、胶结液与脲酶溶液的质量比,以及各添加剂的掺量范围,实现了酶诱导碳酸盐沉淀反应过程中流变性能与碳酸钙沉积效率的协同优化,显著提升了回填材料的导热性能、水稳定性、热稳定性及力学性能,有效解决了现有回填材料导热系数低、水稳定性差、高低温环境下性能衰减严重的缺陷。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This application belongs to the technical field of ground source heat pump backfill materials, specifically relating to a ground source heat pump EICP mortar backfill material, its preparation method and application. Background Technology
[0002] Ground source heat pumps utilize shallow geothermal energy for building heating and cooling, offering energy-saving and environmental advantages. The backfill material, acting as the heat transfer medium between the underground heat exchanger and the surrounding soil and rock, directly determines the system's heat exchange efficiency; simultaneously, it must possess excellent water stability, thermal stability, and suitable mechanical properties to adapt to complex underground operating conditions.
[0003] Currently, most ground source heat pump projects use the original soil backfill method. This method damages the original physical structure of the soil, resulting in a significant decrease in thermal conductivity and a substantial reduction in the system's heat exchange efficiency. Existing improved backfill materials are mainly divided into two categories: cement-based and bentonite-based. Cement-based materials have better thermal conductivity, but in areas with abundant groundwater, they are easily eroded and peeled off by water flow, creating internal pores and causing long-term performance degradation. Bentonite-based materials improve thermal conductivity by relying on their water retention properties, but their mechanical strength is relatively low. Furthermore, neither type of material can effectively solve the problem of performance degradation under alternating high and low temperature conditions.
[0004] In recent years, microbial induced carbonate precipitation (MICP) technology has been attempted for modifying backfill materials. It utilizes microbial metabolism to generate calcium carbonate deposits that fill internal pores, improving material density and thermal conductivity. However, this technology suffers from limitations in engineering applications, including complex microbial cultivation processes, high environmental adaptability requirements, potential biosafety risks, and low consolidation efficiency. As an alternative, enzyme-induced carbonate precipitation (EICP) directly introduces urease to catalyze calcium carbonate precipitation, simplifying construction processes and reducing application costs. Furthermore, free urease molecules are small in size and have excellent permeability, showing promising application prospects in soil solidification and concrete repair. Nevertheless, existing solidification materials prepared based on enzyme-induced carbonate precipitation technology still have significant shortcomings: On the one hand, the low deposition efficiency of calcium carbonate makes it difficult for the material's density and mechanical properties to meet the actual requirements of ground source heat pump backfilling. On the other hand, there is room for improvement in the thermal conductivity, water stability and thermal stability of the material. In particular, in underground high and low temperature alternation and water erosion environments, problems such as thermal conductivity decay, mass loss and structural disintegration are likely to occur, which limits its engineering application in ground source heat pump systems.
[0005] Therefore, how to develop a backfill material that can take into account good thermal conductivity, excellent water stability, suitable mechanical strength and long-term thermal stability, and overcome the defects of low deposition efficiency and poor overall performance in the existing enzyme-induced carbonate precipitation technology, is a technical problem that urgently needs to be solved in this field. Summary of the Invention
[0006] To address the problems of poor thermal conductivity, insufficient water and thermal stability, low calcium carbonate deposition efficiency, and significant performance degradation under high and low temperature cycling in existing ground source heat pump backfill materials, this application provides a ground source heat pump EICP mortar backfill material, the technical solution of which is as follows: This application provides a ground source heat pump EICP mortar backfill material, which includes basic aggregate, cementing liquid, urease solution, thickener, and thermal conductivity enhancement material; the mass ratio of the basic aggregate, cementing liquid, and urease solution is 100:25:25; the cementing liquid is an aqueous solution containing calcium source and urea; the thickener is hydroxypropyl methylcellulose (HPMC) and xanthan gum (XG), the amount of hydroxypropyl methylcellulose added is 0.4% to 0.6% of the mass of the cementing liquid, and the amount of xanthan gum added is 0.05% to 0.1% of the mass of the cementing liquid; the thermal conductivity enhancement material is carbon fiber (CF) and oyster shell powder (OSP), the amount of carbon fiber added is 2% to 6% of the mass of the basic aggregate, and the amount of oyster shell powder added is 5% to 15% of the mass of the basic aggregate.
[0007] Furthermore, the concentration of calcium acetate in the cementing solution is 1.0 mol / L, and the concentration of urea is 1.5 mol / L.
[0008] Furthermore, the urease solution is a soybean urease solution with a concentration of 1.0 mol / L to 1.5 mol / L.
[0009] Furthermore, the carbon fiber has a length of 1 mm, and the oyster shell powder has a particle size of 500 mesh.
[0010] Further, the amount of hydroxypropyl methylcellulose added is 0.45% of the mass of the cementitious solution, the amount of xanthan gum added is 0.08% of the mass of the cementitious solution, the amount of carbon fiber added is 4.5% of the mass of the basic aggregate, and the amount of oyster shell powder added is 10.5% of the mass of the basic aggregate.
[0011] Furthermore, the basic aggregate is standard quartz sand with a particle size of 0.1 mm to 0.5 mm.
[0012] This application also provides a method for preparing the above-mentioned ground source heat pump EICP mortar backfill material, comprising the following steps: S1: Extraction of urease solution: Mix soybean flour and deionized water at a solid-liquid ratio of 1:10 g / mL, stir and centrifuge, take the supernatant and filter to obtain soybean urease solution, and adjust its concentration to 1.0 mol / L to 1.5 mol / L; S2: Preparation of cementing solution: Prepare an aqueous solution containing 1.0 mol / L calcium acetate and 1.5 mol / L urea to obtain a cementing solution. Then add hydroxypropyl methylcellulose and xanthan gum to the aqueous solution and stir until completely dissolved to obtain solution M. S3: Pre-treated thermally conductive reinforcing material: carbon fiber is mixed with oyster shell powder and then dried; S4: Mixing and preparing mortar: Dry mix the basic aggregate with the carbon fiber and oyster shell powder treated in step S3, then add the solution M prepared in step S2 and the urease solution obtained in step S1, and wet mix evenly to obtain mortar. S5: Molding and curing: Inject the mortar obtained in step S4 into the mold, vibrate to vent the air, and then cure to obtain the ground source heat pump EICP mortar backfill.
[0013] Further, the centrifugation conditions in step S1 are: temperature 20℃, rotation speed 4000r / min, and time 30min; the stirring temperature in step S2 is 28℃ and the time is 25min; and the drying temperature in step S3 is 105℃ and the time is 2.5h.
[0014] Furthermore, the curing conditions described in step S5 are: temperature 23-27℃, relative humidity 60%-80%, time 7 days, and during the curing period, an enzyme-induced carbonate precipitation solution is sprayed onto the mortar surface every 12 hours to maintain humidity.
[0015] This application also provides an application of the above-mentioned EICP mortar backfill material in a ground source heat pump system, wherein the backfill material is filled into the borehole of the underground heat exchanger of the ground source heat pump as a heat transfer medium between the heat exchanger and the surrounding rock and soil, for use in shallow geothermal environments or shallow thermal storage environments.
[0016] This EICP mortar backfill material is used for backfilling boreholes in underground heat exchangers of ground source heat pump systems, serving as a heat transfer medium between the heat exchanger and the surrounding soil and rock. It is particularly suitable for: Shallow geothermal energy (burial depth <200 m, temperature <30℃); Shallow thermal reservoirs (temperature 71–145℃, such as geothermal anomaly areas in Fujian, etc.); The service environment is characterized by abundant groundwater and fluctuating high and low temperatures.
[0017] Based on the above, the ground source heat pump EICP mortar backfill material provided in this application has the following advantages compared with the prior art: By using hydroxypropyl methylcellulose and xanthan gum as compound thickeners, and introducing carbon fiber and oyster shell powder as compound thermally conductive reinforcing materials, while strictly controlling the mass ratio of base aggregate, cementitious liquid and urease solution, as well as the dosage range of each additive, the rheological properties and calcium carbonate deposition efficiency during the enzyme-induced carbonate precipitation reaction were synergistically optimized. This significantly improved the thermal conductivity, water stability, thermal stability and mechanical properties of the backfill material, effectively solving the defects of existing backfill materials such as low thermal conductivity, poor water stability and severe performance degradation under high and low temperature environments. Detailed Implementation
[0018] The present application will now be described in further detail with reference to the embodiments. It is to be understood that the specific embodiments described herein are merely illustrative of the invention and not intended to limit the invention.
[0019] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other.
[0020] To verify the effectiveness of this application, the following embodiments and comparative examples are provided: I. Implementation Examples Example 1 Composition and proportions: 1000g of standard quartz sand (particle size 0.1-0.5mm); 250g of cementing solution (an aqueous solution containing 1.0mol / L calcium acetate and 1.5mol / L urea); 0.4% HPMC and 0.1% XG by mass of cementing solution, i.e., 1.0g HPMC and 0.25g XG; 250g urease solution (soybean urease, concentration 1.5mol / L); 50g carbon fiber (1mm); 100g oyster shell powder (500 mesh).
[0021] Preparation method: (1) Extraction of soybean urease solution: 100g of soybean powder is mixed with 1000mL of deionized water, stirred at room temperature for 15min, centrifuged at 20℃ and 4000r / min for 30min, the supernatant is filtered, and the concentration is adjusted to 1.5mol / L. (2) Preparation of cementing solution: 250g of aqueous solution containing 1.0mol / L calcium acetate and 1.5mol / L urea is prepared, 1.0g of HPMC and 0.25g of XG are added, and stirred at 28℃ for 25min. (3) Pretreatment of thermally conductive reinforcing material: carbon fiber and oyster shell powder are mixed and dried at 105℃ for 2.5h. (4) Dry mixing: Quartz sand is stirred with pretreated carbon fiber and oyster shell powder for 8min. (5) Wet mixing: cementing solution and urease solution are added and stirred for 25min. (6) Molding and curing: Inject into a 50×50×50mm mold, vibrate to vent air, and cure at 23~27℃ and 70% relative humidity for 7 days (spray a small amount of EICP solution every 12 hours). After demolding, dry at 60℃ for 2 days.
[0022] Performance test results: see Table 1.
[0023] Microstructure: SEM showed that the thickener formed a continuous network structure, providing nucleation sites for calcium carbonate; calcium carbonate was uniformly deposited, mainly in the form of aragonite; carbon fibers were uniformly dispersed, with calcium carbonate adhering to the surface to form an anchoring structure; oyster shell powder filled the micropores. XRD showed that calcium carbonate diffraction peaks were strong, mainly in the form of aragonite, with a small amount of calcite.
[0024] Example 2 Composition and proportions: 1000g of standard quartz sand; 250g of cementing solution (containing an aqueous solution of 1.0mol / L calcium acetate and 1.5mol / L urea); 0.6% HPMC and 0.05% XG by mass of cementing solution, i.e., 1.5g HPMC and 0.125g XG; 250g urease solution (concentration 1.0mol / L); 20g carbon fiber (1mm); 50g oyster shell powder (500 mesh).
[0025] Preparation method: Same as in Example 1, except that the urease concentration was adjusted to 1.0 mol / L.
[0026] Performance test results: see Table 1.
[0027] Microstructure: SEM showed that the thickener had a dense network structure but low XG content, fewer nucleation sites, and slightly lower calcium carbonate deposition; the carbon fiber spacing was relatively large, resulting in slightly poor thermal conductivity network continuity; the oyster shell powder had good filling effect, but some micropores remained unfilled. XRD showed moderate diffraction peak intensity.
[0028] Example 3 (Optimal Ratio) Composition and proportions: 1000g of standard quartz sand; 250g of cementing solution (an aqueous solution containing 1.0mol / L calcium acetate and 1.5mol / L urea); 0.45% HPMC and 0.08% XG by mass of cementing solution, i.e., 1.125g HPMC and 0.2g XG; 250g of urease solution (concentration 1.5mol / L); 45g of carbon fiber (1mm); 105g of oyster shell powder (500 mesh).
[0029] Preparation method: Same as in Example 1 (urease concentration 1.5 mol / L).
[0030] Performance test results: see Table 1.
[0031] Microstructure: SEM shows that the thickener forms a uniform and continuous network structure, calcium carbonate is densely and uniformly deposited, and the crystal form is mainly aragonite in spherical / clustered shapes; carbon fibers are uniformly dispersed and form a strong anchoring structure with calcium carbonate, and the fibers are bridged by the thickener to form a three-dimensional thermally conductive network; oyster shell powder fully fills the micropores, resulting in high matrix density. XRD shows that calcium carbonate has the highest diffraction peak intensity, is mainly aragonite, and contains calcite and a small amount of aragonite, with good crystal stability.
[0032] Example 4 Composition and proportions: 1000g of standard quartz sand; 250g of cementing solution (an aqueous solution containing 1.0mol / L calcium acetate and 1.5mol / L urea); 0.5% HPMC and 0.075% XG by mass of cementing solution, i.e., 1.25g HPMC and 0.1875g XG; 250g of urease solution (concentration 1.0mol / L); 30g of carbon fiber (1mm); 80g of oyster shell powder (500 mesh).
[0033] Preparation method: Same as in Example 1 (urease concentration 1.0 mol / L).
[0034] Performance test results: see Table 1.
[0035] Microstructure: SEM showed that the thickener network structure was intact, and the calcium carbonate deposition was uniform, but the amount produced was slightly lower than in Example 3 due to the lower urease concentration; the carbon fiber was well dispersed, forming a local thermally conductive network, but the continuity was slightly inferior; oyster shell powder filled most of the pores. XRD showed good diffraction peak intensity, with aragonite as the main component.
[0036] Table 1 Performance test results of the embodiments
[0037] Note: The optimal ratio has a slightly higher proportion of organic matter and a slightly lower thermogravimetric residue, but its overall durability is better.
[0038] II. Comparative Example Comparative Example 1 (without thermally conductive reinforcing material): Same as Example 3, but without CF and OSP. Performance is shown in Table 2.
[0039] Comparative Example 2 (single thickener, HPMC only): Same as Example 3, but only HPMC (0.53%) was added to the binder, without XG. Performance is shown in Table 2.
[0040] Comparative Example 3 (Backfilling with original soil): The original soil at the construction site was dried and sieved. Properties are shown in Table 2.
[0041] Comparative Example 4 (HPMC and XG below the lower limit): Same as Example 3, but HPMC 0.2% and XG 0.02%. Performance is shown in Table 2.
[0042] Table 2 Performance test results for Comparative Examples 1-4
[0043] "—" indicates that the test was not performed or the data is unavailable for that pair.
[0044] Comparative Example 5 (HPMC and XG are above the upper limit): Same as Example 3, but HPMC 0.8% and XG 0.15%. Performance is shown in Table 3.
[0045] Comparative Example 6 (Carbon fiber only): Same as Example 3, but without OSP. Performance is shown in Table 3.
[0046] Comparative Example 7 (Oyster shell powder only): Same as Example 3, but without CF. Performance is shown in Table 3.
[0047] Comparative Example 8 (carbon fiber length 3mm): Same as Example 3, but with a CF length of 3mm. Performance is shown in Table 3.
[0048] Table 3 Performance test results for comparative examples 5-8
[0049] Comparative Example 9 (carbon fiber length 6mm): Same as Example 3, but CF length 6mm. Performance is shown in Table 4.
[0050] Comparative Example 10 (oyster shell powder, 300 mesh): Same as Example 3, but OSP particle size is 300 mesh. Performance is shown in Table 4.
[0051] Comparative Example 11 (carbon fiber content exceeds the upper limit: 7%): Same as Example 3 but CF 70g (7%). Performance is shown in Table 4.
[0052] Comparative Example 12 (oyster shell powder content exceeds the upper limit: 16%): Same as Example 3 but OSP 160g (16%). Performance is shown in Table 4.
[0053] Table 4 Performance test results for comparative examples 9-12
[0054] Note: When the carbon fiber content exceeds 6%, it may lead to an increased fiber aggregation effect, and the thermal conductivity will no longer improve or may even decrease.
[0055] Comparative Example 13 (HPMC content exceeds the upper limit: 0.8%): Same as Example 3, but HPMC 0.8%, XG remains at 0.08%. Performance is shown in Table 5.
[0056] Comparative Example 14 (XG doping exceeds the upper limit: 0.15%): Same as Example 3, but XG 0.15%, HPMC 0.45%. Performance is shown in Table 5.
[0057] Table 5 Performance test results of comparative examples 13-14
[0058] III. Summary of Results All of the above Examples 1-4 are within the proportions declared in the technical solution of this application. Their thermal conductivity is ≥1.70 W / (m·K), water immersion strength loss rate is ≤10%, disintegration rate is ≤3.0%, thermal conductivity decreases by ≤8% after 8 cycles at 80℃, and mass loss rate is ≤5.5%, which is significantly better than the comparative example. Among them, Example 3 (optimal proportion) has the best effect: thermal conductivity is 1.99 W / (m·K), water immersion strength loss rate is only 7.5%, disintegration rate is only 1.7%, thermal conductivity decreases by only 5% after high and low temperature cycling, and mass loss is only 3.8%.
[0059] Microstructural analysis showed that the thickener in Example 3 formed a uniform network structure, the calcium carbonate was densely deposited and had a stable crystal form (mainly aragonite), the carbon fibers were uniformly dispersed and formed an anchoring structure with the calcium carbonate, thus constructing a continuous three-dimensional thermally conductive network. The oyster shell powder fully filled the pores, achieving synergistic optimization of thermal conductivity, mechanics and stability.
[0060] Comparative Examples 1-14, from the perspectives of no thermally conductive reinforcing material, single thickener, original soil backfill, thickener below / above the upper / lower limits, single thermally conductive reinforcing material, CF length exceeding the range, OSP particle size exceeding the range, and the dosage of each component exceeding the upper limit, fully demonstrate the rationality and critical significance of the components and proportion ranges of this application. Any adjustment beyond the scope of this application will lead to a significant deterioration in the thermal conductivity, water stability, thermal stability, or mechanical properties of the backfill material, failing to meet the engineering requirements of ground source heat pump backfill materials.
[0061] Therefore, this application achieves a comprehensive improvement in the overall performance of backfill material through the synergistic effect of specific components and proportions, demonstrating significant progress and industrial applicability.
[0062] In summary, this application addresses the shortcomings of existing technologies by providing the aforementioned EICP mortar backfill material for ground source heat pumps, its preparation method, and its application. The design concept and resulting beneficial effects of this application are as follows: I. Design Concept (Key Innovations) Synergistic Regulation of Thickener Compounding: This application overcomes the limitation of single thickeners in achieving both rheological properties and mineralization efficiency by, for the first time, compounding hydroxypropyl methylcellulose (HPMC) and xanthan gum (XG) in a specific ratio (HPMC 0.4%–0.6%, XG 0.05%–0.1%). The polymer network of HPMC enhances the mortar's resistance to water dispersion and its workability, while the hydroxyl groups and negative charge of XG adsorb calcium ions and provide nucleation sites for calcium carbonate, compensating for the inhibitory effect of HPMC on mineralization. This achieves synergistic optimization of rheological properties and calcium carbonate deposition efficiency.
[0063] Thermal conductivity enhancement material composite thermal conductivity mechanism: This application combines short-cut carbon fibers (1 mm) with oyster shell powder (500 mesh) in a specific ratio (CF 2%–6%, OSP 5%–15%). The carbon fibers construct a continuous three-dimensional thermal conductivity network and form an "anchoring" structure with calcium carbonate to enhance mechanical properties; the oyster shell powder, as an exogenous calcium carbonate, participates in the EICP mineralization reaction, while its fine particles effectively fill the tiny pores between sand grains, reducing air retention and lowering interfacial thermal resistance, forming a complementary and synergistic mechanism of "long-range thermal conductivity channels + local pore filling".
[0064] Optimization of cementing solution for geothermal environment: This application selects 1.0 mol / L calcium acetate to replace traditional calcium chloride for shallow geothermal environments (20-28℃, pH 6.5-8.0) to avoid chloride ion pollution, and the acetate ions can be degraded by underground microorganisms; the urea concentration of 1.5 mol / L is matched with the urease concentration of 1.0-1.5 mol / L to ensure that the urease maintains high catalytic activity within the shallow geothermal temperature range, and solves the problems of low calcium carbonate yield and unstable solidification effect.
[0065] Optimal proportion design: Determine the optimal proportion (HPMC 0.45%, XG 0.08%, CF 4.5%, OSP 10.5%) and reasonable range to ensure the best balance of thermal conductivity, water stability, thermal stability and mechanical properties.
[0066] Engineering adaptability of the preparation process: The EICP mortar preparation process was optimized, including low-temperature centrifugal extraction of soybean urease, low-temperature dispersion of thickener, pretreatment and drying of thermally conductive reinforcing materials, sequential control of "dry mixing-wet mixing-molding-curing", and a cementitious liquid:urease:sand mass ratio of 1:1:4, ensuring sufficient EICP reaction and suitable workability of the mortar. During curing, EICP solution is periodically sprayed to maintain humidity. The process is simple, highly repeatable, and suitable for large-scale application.
[0067] II. Beneficial Effects Significantly improved thermal conductivity: The optimal thermal conductivity reaches 1.99 W / (m·K), which is higher than that of materials without thermal conductivity reinforcement and higher than that of original soil backfill. This can reduce the design length of buried pipes and lower the initial investment of the system.
[0068] Excellent water stability: The optimal ratio has a surface strength of 13.2 MPa, a water immersion strength loss rate of only 7.5%, and a disintegration rate of only 1.7%. Compared with materials without thermal conductivity reinforcement, the surface strength is improved, the water immersion strength loss rate is reduced, and the disintegration rate is reduced, effectively resisting groundwater erosion.
[0069] Excellent thermal stability: 81.6% of the thermogravimetric residual mass at 800℃; after 8 cycles of high and low temperature at 80℃, the thermal conductivity decreases by only 5%, and the mass loss rate is only 3.8%, which is significantly better than the existing technology. It can adapt to the long-term high and low temperature alternating service environment of ground source heat pumps and geothermal anomaly areas.
[0070] Suitable mechanical properties: ensuring borehole wall stability and preventing borehole collapse, while avoiding excessive strength that would prevent excavation during maintenance, thus balancing safety and maintainability.
[0071] Environmentally friendly: Calcium acetate replaces calcium chloride to avoid chloride ion pollution; soybean urease is a natural plant-derived enzyme with no biosafety risks; oyster shell powder is a resource utilization of waste shells, and carbon fiber is recycled from industrial waste; the preparation has low energy consumption and the construction cost is lower than that of MIP technology.
[0072] It has strong adaptability: it can maintain good performance under conditions of urease concentration of 1.0-1.5 mol / L, pH of 6.5-8.0 and temperature of 20-28℃, and still performs well in geothermal anomaly areas (71-145℃), making it widely applicable.
[0073] In summary, this application, through the above design concept, successfully achieves a synergistic improvement in the thermal conductivity, water stability, thermal stability, and mechanical properties of EICP mortar backfill material, providing a highly efficient, durable, green, and economical backfill solution for ground source heat pump systems, and has significant creative and industrial practical value.
[0074] It should be noted that: (1) The test methods for each performance index in this application are as follows, and all tests are conducted in accordance with national standards or methods recognized in the field: Thermal conductivity: The Hot Disk thermal constant analyzer (transient plane heat source method) was used. Before the test, the samples were cured in saturated water at 25℃ for 28 days. During the test, the probe was clamped between two 50×50×50mm samples, the test power was 0.5W, the test time was 160s, and 3 parallel samples were tested in each group. The average value was taken.
[0075] 7-day compressive strength: Unconfined compressive strength test was conducted according to GB / T 17671-1999 "Test Method for Strength of Cement Mortar (ISO Method)". The specimen size was a Φ50×100mm cylinder, with a loading rate of 1mm / min. The maximum load at failure was recorded, and the compressive strength was calculated using the formula σ=P / A. Three parallel specimens were used in each group, and the average value was taken.
[0076] Surface strength: Micro-penetration method was used, employing an Edberg digital push-pull force gauge with a probe cross-sectional area of 28.5 mm². 2 The peak penetration force on the surface of the test specimen was measured, and the surface strength was calculated using the formula q=f / s. Three parallel specimens were used in each group, and the average value was taken.
[0077] Water immersion strength loss rate: The sample is completely immersed in deionized water for 12 hours, then drained and dried at 60°C to constant weight. The surface strength after drying is tested, and the strength loss rate is calculated according to the formula L=(q_before - q_after) / q_before×100%.
[0078] Disintegration rate: Cut a 50×50×10mm test block, weigh the initial mass M0, soak it in deionized water for 12h (water depth at least 2cm), take it out and dry it at 60℃ to constant weight, weigh the mass M1 after drying, and calculate the disintegration rate according to the formula D=(M0-M1) / M0×100%.
[0079] Thermogravimetric residual mass: Thermogravimetric analyzer (NETZSCH TG209F3, Germany), temperature range RT-800℃, heating rate 10℃ / min, nitrogen atmosphere, recorded the percentage of residual mass of the sample at 800℃.
[0080] Thermal conductivity decrease and mass loss after high and low temperature cycling at 80℃: The sample was placed at a low temperature of 15℃ for 12 hours and a high temperature of 80℃ for 12 hours as one cycle. After a total of 8 cycles, the thermal conductivity and mass were tested, and the decrease rate and loss rate were calculated.
[0081] (2) Definition: In this article, “~” is used to represent the range of values, and the range of values represented by this expression includes two endpoint values.
[0082] EICP is an abbreviation for Enzyme-Induced Carbonate Precipitation.
[0083] (3) Raw materials used in implementation: All enzymes used in this article are commercially available enzymes that can be purchased and obtained by those skilled in the art.
[0084] In summary, the specific parameters or some commonly used reagents or raw materials in the above embodiments are specific or preferred embodiments under the concept of this application, and not limitations thereof; those skilled in the art can make adaptive adjustments within the concept and protection scope of this application.
[0085] In addition, unless otherwise specified, the raw materials used may be commercially available products in the field or prepared by conventional methods in the field; that is, the reagents and instruments used in this embodiment do not specify the manufacturer or other information, and are all conventional products that can be purchased from the market.
[0086] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
[0087] The specific embodiments of this application have been described above, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.
Claims
1. A type of EICP mortar backfill material for ground source heat pumps, characterized in that, Includes basic aggregates, binder, urease solution, thickener, and thermally conductive reinforcing materials; The mass ratio of the basic aggregate, cementitious liquid and urease solution is 100:25:25; The basic aggregate is standard quartz sand with a particle size of 0.1 mm to 0.5 mm; The cementing solution is an aqueous solution containing a calcium source and urea; wherein the calcium source is calcium acetate, the concentration of calcium acetate in the cementing solution is 1.0 mol / L, and the concentration of urea is 1.5 mol / L; The urease solution is a soybean urease solution with a concentration of 1.0 mol / L to 1.5 mol / L; The thickener is hydroxypropyl methylcellulose and xanthan gum, wherein the amount of hydroxypropyl methylcellulose added is 0.45% of the mass of the cementitious solution, and the amount of xanthan gum added is 0.08% of the mass of the cementitious solution. The thermally conductive reinforcing material is carbon fiber and oyster shell powder. The amount of carbon fiber added is 4.5% of the mass of the base aggregate, and the amount of oyster shell powder added is 10.5% of the mass of the base aggregate. The length of the carbon fiber is 1 mm, and the particle size of the oyster shell powder is 500 mesh.
2. A method for preparing EICP mortar backfill material for ground source heat pumps according to claim 1, characterized in that, Includes the following steps: S1: Extraction of urease solution: Mix soybean flour and deionized water at a solid-liquid ratio of 1:10 g / mL, stir and centrifuge, take the supernatant and filter to obtain soybean urease solution, and adjust its concentration to 1.0 mol / L to 1.5 mol / L; S2: Preparation of cementing solution: Prepare an aqueous solution containing 1.0 mol / L calcium acetate and 1.5 mol / L urea to obtain a cementing solution. Then add hydroxypropyl methylcellulose and xanthan gum to the aqueous solution and stir until completely dissolved to obtain solution M. S3: Pre-treated thermally conductive reinforcing material: carbon fiber is mixed with oyster shell powder and then dried; S4: Mixing and preparing mortar: Dry mix the basic aggregate with the carbon fiber and oyster shell powder treated in step S3, then add the solution M prepared in step S2 and the urease solution obtained in step S1, and wet mix evenly to obtain mortar. S5: Molding and curing: Inject the mortar obtained in step S4 into the mold, vibrate to vent the air, and then cure to obtain the ground source heat pump EICP mortar backfill.
3. The preparation method according to claim 2, characterized in that, The centrifugation conditions in step S1 are: temperature 20℃, rotation speed 4000r / min, and time 30min; the stirring temperature in step S2 is 28℃ and the stirring time is 25min; the drying temperature in step S3 is 105℃ and the drying time is 2.5h.
4. The preparation method according to claim 2, characterized in that, The curing conditions described in step S5 are: temperature 23-27℃, relative humidity 60%-80%, time 7 days, and during the curing period, an enzyme-induced carbonate precipitation solution is sprayed onto the mortar surface every 12 hours to maintain humidity.
5. The application of the EICP mortar backfill material for ground source heat pumps according to claim 1 in a ground source heat pump system, characterized in that: The backfill material is filled into the borehole of the underground heat exchanger of the ground source heat pump, serving as a heat transfer medium between the heat exchanger and the surrounding rock and soil, for use in shallow geothermal environments or shallow thermal storage environments.
Citation Information
Patent Citations
Soil body reinforcement research method based on improved EICP technology and application
CN115032365A
Method for inducing mineralization and reinforcement of sandy soil by introducing carboxymethyl cellulose and urease
CN117285934A